Comparison of flip-flow screen and circular vibrating screen vibratory sieving processes for sticky fine particles. (September 2022) - Yu, Chi; Pu, Kunwei; Geng, Runhui; Qiao, Dezheng; Lin, Dongdong; Xu, Ningning; Wang, Xinwen; Li, Jinwu; Gong, Sanpeng; Zhou, Qiang
Highlights: The VFFS was used for the classification of sticky fine materials. A five-degree-of-freedom dynamic model and equations of VFFS were established. The screening experiments of sticky fine particles in CVS and VFFS were conducted. A good performance of VFFS was illustrated for screening 3 mm sticky fine materials. Abstract: Screening is a separation process that classifies materials according to their particle size and is a key unit for mineral processing and utilization. Recently, vibrating flip-flow screens (VFFSs) characterized by large vibration intensity of the screen surface and high efficiency for sticky fine particles have been widely applied. Unlike the traditional vibrating screens, the VFFS is a two-body vibration system, including two vibrating bodies, comprising the main screen frame and a floating screen frame. In this paper, a single-deck type of 0827 VFFS excited by an exciter was designed and produced, and a five-degree-of-freedom translational and rotational dynamic model and equations reflecting the VFFS's motion behavior were established. Then, the dynamic characteristics and spatial trajectories of the main and floating screen frame were investigated through the theoretical analysis and vibration testing. When the connecting stiffness between these two screen frames is very large, the two-body VFFS becomes a single-body circular vibrating screen (CVS). Through screening experiments on the CVS and VFFS, the screening behaviors of sticky fine materials were further studied. The results show a phenomenon of fine particles adhering to the screen surface in the process of screening the sticky fine materials with the CVS. In addition, due to the effects of adhesion and agglomeration, 3–1 mm and 1–0 mm particles cannot easily pass through the screen aperture. The screening efficiency is only 61.99 %, and the total misplaced materials is 9.82 % in the CVS. Compared with the CVS, due to the larger vibration intensity of the sieve mat in the VFFS, there are almost no adhered fine particles on the screen surface. Furthermore, the larger vibration acceleration of the screen surface can improve the desorption and depolymerization of fine particles. Therefore, the screening performance of the VFFS is significantly better than the CVS, with a screening efficiency of 77.62 % and total misplaced materials of 5.76 %.